2007
DOI: 10.1128/ec.00330-05
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Magnaporthe grisea Avirulence Gene ACE1 Is Connected to the Initiation of Appressorium-Mediated Penetration

Abstract: Magnaporthe grisea is responsible for a devastating fungal disease of rice called blast. Current control of this disease relies on resistant rice cultivars that recognize M. grisea signals corresponding to specific secreted proteins encoded by avirulence genes. The M. grisea ACE1 avirulence gene differs from others, since it controls the biosynthesis of a secondary metabolite likely recognized by rice cultivars carrying the Pi33 resistance gene. Using a transcriptional fusion between ACE1 promoter and eGFP, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
67
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 51 publications
5
67
0
2
Order By: Relevance
“…The only other PKS/NRPS that is known to be involved in plant-fungus interactions is Ace1 of M. grisea. Ace1 putatively encodes an unidentified secondary metabolite that acts as an avirulence factor during interactions with rice cultivars harbouring the Pi33 'R' gene triggering a hypersensitive response in a gene-for-gene fashion (Böhnert et al, 2004;Collemare et al, 2008a, b;Fudal et al, 2007;Khaldi et al, 2008;Vergne et al, 2007). This gene is expressed specifically in the appressoria of M. grisea, and the metabolite produced by this gene cluster has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only other PKS/NRPS that is known to be involved in plant-fungus interactions is Ace1 of M. grisea. Ace1 putatively encodes an unidentified secondary metabolite that acts as an avirulence factor during interactions with rice cultivars harbouring the Pi33 'R' gene triggering a hypersensitive response in a gene-for-gene fashion (Böhnert et al, 2004;Collemare et al, 2008a, b;Fudal et al, 2007;Khaldi et al, 2008;Vergne et al, 2007). This gene is expressed specifically in the appressoria of M. grisea, and the metabolite produced by this gene cluster has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…These phytotoxins act as virulence factors (Walton et al, 2004;Hoffmeister & Keller, 2007;Walton, 2006;Johnson et al, 2000;Elliott et al, 2007). Additionally, a PKS/NRPS hybrid enzyme (Ace1) of Magnaporthe grisea acts as an avirulence factor, triggering resistance in selective rice cultivars harbouring the corresponding resistance gene Pi33 (Böhnert et al, 2004;Collemare et al, 2008a, b;Fudal et al, 2007;Khaldi et al, 2008;Vergne et al, 2007). A recent comparative genomics study revealed that the genomes of the two biocontrol species T. virens and Trichoderma atroviride harbour a large number of NRPS and PKS genes, and the genome of T. virens contains more NRPSs than any other filamentous fungi studied so far (Kubicek et al, 2011 …”
Section: Introductionmentioning
confidence: 99%
“…However, further experiments are needed to clarify that hypothesis. ACE1 gene expression has been reported that the expression is connected to the onset of appressorial-mediated penetration using a transcriptional fusion between ACE1 promoter and eGFP [12], therefore, this EGFP reporter method might be applicable for the expression monitoring other AVR genes in M. oryzae.…”
Section: Discussionmentioning
confidence: 99%
“…To date, ~85 blast R genes have been identified [6]. In Japanese rice cultivars, thirteen dominant genes (Pish, Pik-h, Pia, Pii, Pik, Pik-m, Piz, Pita, Pita-2, Piz-t, Pik-p, Pib, and Pit) have been identified, while twenty -five avirulence genes of M. oryzae have been genetically mapped [7], nine of which were recently isolated, AVRPita [8], AVR-CO39 [9], PWL1 [10], PWL2 [11], ACE1 [12], AVR-Pizt [13], AVR-Pia [14], [15], AVR-Pii, and AVR-Pik/km/kp [16]. The avirulence genes PWL1 and PWL2, isolated by map-based cloning are responsible for the nonpathogenicity of rice pathogenic strains of M. oryzae against Eragrostis curvula, weeping lovegrass [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…1) Several avirulence factors have been reported from Pyricularia isolates in rice. [2][3][4] Blast fungi might also produce active factors such as host-specific toxins which some fungal pathogens produce as determinants of pathogenicity. 5) Virulence agents produced by Pyricularia isolates have also been examined.…”
mentioning
confidence: 99%